Tracing Corrupt Politician Via Anti-Money Laundering Regime: Malaysian Experience - A. Rahman, Aspalella (2022)
It is generally accepted that corrupt politician can be found in almost any country. Due to the position held and influence potentially formed over others, a politician is at higher risk for involvement in corruption or any other financial crimes. This paper provides an analysis of the anti-money laundering (AML) laws that affect the confiscation of the illegal proceeds derived from coffuption committed by politician against the backdrop of Malaysian law. This paper mainly relies on statutes and court cases as its primary sources of information. It is supported by secondary data to justify the analysis. This paper also utilized analytical descriptive approach to analyze relevant provisions from statutes and to examine current court cases regarding the implementation of the AML laws to combat corruption among politician. It is submitted that the AML legislation has comprehensive provisions that can be utilized to detect and confiscate the ill-gotten gains from corrupt politicians. This regime if effectively invoked, can help to reduce the corruption activities in Malaysia. However, when the illegal proceeds evolved globally, it will pose significant hurdles for the enforcement authorities as it needs great cooperation from their international counterparts to give evidence against the perpetrators. To make matters worse, some of the evidences went missing and even the witnesses are absconded or refuse to give cooperation. Indeed, getting the full cooperation and evidence from overseas is a difficult exercise. Therefore, the concerted efforts among all the relevant parties are critical to minimize the problems in this area of concern.